PENGARUH KONSUMSI KACANG HIJAU TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI DI PUSKESMAS KEBUN KOPI - Imelda, Imelda; Rosmaria, Rosmaria; Saputri, Vivin Nofrianti (NHM PRESS, 2024)
According to WHO, the average rate of exclusive breastfeeding in the world is only 38%. Based on data from the Ministry of Health of Indonesia in 2023, the coverage of exclusive breastfeeding nationally is only 63.9% and in Jambi Province it is 66%. According to the Jambi City Health Office, in 2022 exclusive breastfeeding was 29.16% and in 2023 it was 68.5%. Based on data from Kebun Kopi Health Center, it was found that as many as 86.7% of babies received exclusive breastfeeding and 3 out of 5 breastfeeding mothers did not give exclusive breastfeeding because of their poor milk production. This study is a pre-experimental study with a one-group pretest-posttest design which aims to see the effect of mung bean consumption on increasing breast milk production in breastfeeding mothers at Kebun Kopi Health Center in 2024. This research was carried out at Kebun Kopi Health Center in 2024 and has been carried out in January-September 2024. The population in this study is breastfeeding mothers with a sample of 30 people using the total sampling technique. The data were analyzed univariate and bivariate using the wilcoxon test because the data were not normally distributed. The results of this study show that the average breast milk production in breastfeeding mothers at Kebun Kopi Health Center in 2024 before mung bean consumption is 33.50 ml. The average milk production in breastfeeding mothers after consuming mung beans for 7 days was 62.33 ml, and there was an effect of mung bean consumption on the increase in breast milk production in breastfeeding mothers at Kebun Kopi health center with a p-value of 0.000. The conclusion of this study is that there is an effect of mung bean consumption on increasing breast milk production in breastfeeding mothers at Kebun Kopi health center